Pengaruh Keaktifan Lansia dalam Mengikuti Kegiatan Posyandu Lansia dengan Kualitas Hidup di Desa Cibadak Kecamatan Cikupa Kabupaten Tangerang - Eliawati, Rizky; Rahmadyanti, Rahmadyanti (Universitas Malahayati, 2024)
ABSTRACT The aging process is a natural process that occurs in the human life cycle which will experience three stages of life from childhood to adulthood and ending with old age. One of the basic service efforts to improve the quality of life of the elderly in non-nursing institutions is the activities of integrated service posts (posyandu) for the elderly. In carrying out posyandu activities there are often obstacles, namely the activeness and enthusiasm of the elderly which are still not optimal. To find out the influence of the elderly's activeness in attending posyandu for the elderly on the quality of life in Cibadak Village, Cikupa District, Tangerang Regency in 2023. This research uses quantitative research methods with a cross sectional design. The population in the study was all elderly people in the Posyandu coverage area in the elderly Posyandu as many as 210 elderly people, a sample of 138 respondents, simple random sampling technique. Univariate and bivariate data analysis used the chi square test. Of the 138 respondents, 80 respondents (58.0%) had a high quality of life. And 63 people are characterized by age 60-63 years, 57 people are predominantly female, 64 people have a history of current illness. Of the 138 respondents, 83 respondents (60.1%) were active in the elderly posyandu activities. And 61 people are characterized by age 60-63 years, 62 people are predominantly female, 70 people have a history of current illness. p-value 0.000 (<0.05). There is a significant influence on the activeness of the elderly in participating in posyandu activities for the elderly with a high quality of life. Keywords: Activeness, Quality of Life, Posyandu for the Elderly ABSTRAK Proses penuaan adalah proses alamiah yang terjadi dalam siklus kehidupan seorang manusia yang akan mengalami tiga tahap fase kehidupan dari anak sampai dewasa dan berakhir dengan usia lanjut. Salah satu upaya pelayanan dasar untuk meningkatkan kualitas hidup lansia di non panti adalah dengan kegiatan pos pelayanan terpadu (posyandu) lansia. Dalam melaksanakan kegiatan posyandu sering terdapat kendala yaitu keaktifan dan antusian lansia yang masih belum optimal. Diketahui pengaruh keaktifan lansia dalam mengikuti posyandu lansia dengan kualitas hidup di Desa Cibadak Kecamatan Cikupa Kabupaten Tangerang tahun 2023.Penelitian ini menggunakan metode penelitian kuantitatif dengan desain cross sectional. populasi dalam penelitian seluruh lansia dalam wilayah jangkauan posyandu di Posyandu lansia sebanyak 210 Lansia, sampel 138 responden, teknik sampling simple random sampling. Analisa data univariate dan bivariate menggunakan uji chi square. Dari 138 responden, yang memiliki kualitas hidup tinggi sebanyak 80 responden (58,0%). Dan memiliki karakteristik umur 60-63 tahun sebanyak 63 orang, jenis kelamin mayoritas perempuan sebanyak 57 orang, Riwayat penyakit sekarang sebanyak 64 orang. Dari 138 responden, yang memiliki keaktifan lansia dalam mengikuti kegiatan posyandu lansia dengan kategori aktif sebanyak 83 responden (60,1%). Dan memiliki karakteristik umur 60-63 tahun sebanyak 61 orang, jenis kelamin mayoritas perempuan sebanyak 62 orang, Riwayat penyakit sekarang sebanyak 70 orang. p-value 0,000 (<0,05). Terdapat pengaruh yang signifikan dari keaktifan lansia dalam mengikuti kegiatan posyandu lansia dengan kualitas hidup tinggi. Kata Kunci: Keaktifan, Kualitas Hidup, Posyandu Lansia